Producción, preproducción y postproducción del tema "El Ropero" de la agrupación "La Qubula" - Romo Legña, Daniel Alejandro (2015)
The main objective of this project was the total production of the single “EL ROPERO”, since the launch by the musicians, the musical concept, through artistic design, until all the stages of musical production which was carried to term processes of mixing and mastering, resulting in a new, fresh and appealing product to the music market. They made a about musical genre, going from blues to funk, taking the most important points to keep as musical exponents reference characteristics. For this we conducted several steps and processes such as pre-production. Where was plan from work, the distribution of resources throughout the production process…